Social risks of international labour migration in the context of global challenges - Aleksandra Kuzior; Anna Liakisheva; Iryna Denysiuk; Halyna Oliinyk; Liudmyla Honchar (Journal of Risk and Financial Management, 2020)
The results of the study of migration risks of labor migrants from Ukraine are presented in this article. The purpose of the study is to find out the differences in the perception of obstacles and risks that arise in the process of work abroad among experienced and potential labour migrants from Ukraine within the cognitive, behavioural, and emotional components of their intercultural competence. The study has been implemented from the standpoint of a set of analytical tools, including: the concept of the advantages of replacing the "risk/reliability" scheme with the "risk/hazard" scheme; views of risk and chance as interrelated variables that motivate people to try to explore the world and overcome obstacles; the concept of "triple individualization"; in a risk society. It has been found that social risks are hidden in the imbalance of intercultural competence of experienced labor migrants and are not realized by potential labor migrants. It has been proven that the greatest social danger for labor migrants from Ukraine is the loss of components of competence and initiative. It has been established that the key points of the comparative analysis of social risks faced by labor migrants from Ukraine open up prospects for improving the methodology for studying social (and socio-cultural, in particular) risks.
Keywords: 330; cross-cultural competence; labour migration; migration flows; social insecurity; social risks